How language affects peer responsiveness in an online cancer support group: implications for treatment design and facilitation. Issue 7 (11th February 2014) - Lewallen, Andrea C.; Owen, Jason E.; Bantum, Erin O'Carroll; Stanton, Annette L.
Abstract Objective Little is known about how positive group interactions develop in online support groups. Previous research suggests that message content, self‐disclosure, and emotional expression may be central to this process. The purpose of this study was to identify linguistic and qualitative characteristics of participants' messages that predict how other participants respond in an asynchronous discussion board for cancer‐related distress. Methods 525 discussion board messages posted by 116 participants in the health‐space.net trial were collected. Linguistic Inquiry and Word Count (2001) was used to identify linguistic markers of emotional expression and pronoun use. Message topics were identified using qualitative analysis. Logistic regression and chi‐square analyses were used to evaluate whether linguistic characteristics and message topics predicted receiving a response from other survivors in the online group. Results Messages were more likely to receive a reply if they had higher word count, OR = 1.30, p = 0.001, or fewer second‐person pronouns, OR = 0.923, p = 0.040. Messages with high levels of positive emotion were less likely to receive a reply, OR = 0.94, p = 0.03. Common message topics related to self‐disclosure (51%), the support group (38.5%), medical experiences (30.9%), and experiences with the website (30.1%). Several message topics were associated with greater likelihood of a reply: self‐disclosure (p < 0.001), medical experiences (p = 0.01), relationship issues (p = 0.05), and introductory posts (p < 0.01). Conclusions Informing participants how to introduce themselves to the group (i.e., detailed and self‐focused messages discussing personal issues such as the effects of illness on life and relationships) could promote cohesion and enhance overall engagement with Internet‐based support groups or interventions. Copyright © 2014 John Wiley & Sons, Ltd.